2018
DOI: 10.1111/apa.14465
|View full text |Cite
|
Sign up to set email alerts
|

Higher daily doses of caffeine lowered the incidence of moderate to severe neurodevelopmental disabilities in very low birth weight infants

Abstract: A higher average daily dose of caffeine citrate was associated with better neurodevelopmental outcomes of VLBW infants. However, the cumulative dose did not have an impact on their short-term or long-term outcomes. Further research is needed to confirm our findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…NLRC4 dependent mechanisms can also contribute to brain injury induced by cerebral ischemia, as has recently been described in a rodent‐based model of stroke [37]. Interestingly, caffeine therapy for the apnea of prematurity, which reduces the incidence of moderate to severe neurodevelopmental disabilities in very low birth weight infants [38], can also reduce NLRC4‐inflammasome activation [39].…”
Section: Discussionmentioning
confidence: 99%
“…NLRC4 dependent mechanisms can also contribute to brain injury induced by cerebral ischemia, as has recently been described in a rodent‐based model of stroke [37]. Interestingly, caffeine therapy for the apnea of prematurity, which reduces the incidence of moderate to severe neurodevelopmental disabilities in very low birth weight infants [38], can also reduce NLRC4‐inflammasome activation [39].…”
Section: Discussionmentioning
confidence: 99%
“…which reduces the incidence of moderate to severe neurodevelopmental disabilities in very low birth weight infants 37 , can also reduce NLRC4-inflammasome activation 38 . 6 7The resolution of inflammation requires neutrophil arrest, death and removal 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Several findings also revealed the benefits of higher doses of caffeine for VLBW preterm infants. A retrospective analysis suggested that a higher average daily dose of caffeine citrate was associated with better neurodevelopmental outcomes in VLBW infants ( Ravichandran et al, 2019 ). Another RCT trial found that a maintenance dose as high as 10 mg/kg better reduced the duration of apnea and caffeine treatment in this population ( Zhang et al, 2019 ).…”
Section: Dosage Of Caffeine In Preterm Infantsmentioning
confidence: 99%
“…Recently, it has also been proposed that individualized caffeine medication can be administered with the help of a physiologic based pharmacokinetics (PBPK) model ( Abduljalil et al, 2020 ; Aranda and Beharry, 2020 ; Verscheijden et al, 2020 ). On the other hand, the clinical response is specific to each individual and influenced by many factors such as gestational age, birth weight and genetic variability ( Gal, 2007 ; Bloch-Salisbury et al, 2010 ; Francart et al, 2013 ; Ravichandran et al, 2019 ; He et al, 2020 ). Although increasing evidence has proven that the higher dose of caffeine is beneficial for newborns, there are also potential toxic risks and unknown long-term safety problems.…”
Section: Therapeutic Drug Monitoring Of Caffeinementioning
confidence: 99%